The Kala Chitta foreland fold and thrust belt, Northern Pakistan (Journal of Nepal Geological Society, 1995)
The present structural framework of the Kala Chitta Range evolved through movement between two detachment surfaces. The Precambrian Attock Slates acted as a basal detachment surface above which large scale horizontal compression took place to produce the main structural framework of the Kala Chitta Range. The Middle Eocene argillaceous and gypsiferous Kuldana Formation behaved as the upper detachment surface giving rise to blind thrusts which were later exposed due to the intense erosion of the overlying folded Miocene strata.